Programa MAIS PAIC: análise da formação continuada de professores alfabetizadores da regional V do município de Fortaleza - Vieira, Flavianne Barreto Santos (2024)
This research aims to evaluate the Literacy at the Right Age Program, which is a public educational policy that aims to meet the proposal of contributing to the needs and challenges of literacy in order to identify the needs and demands of schools in the process of continued training. In this attempt, we seek to discuss the issues that permeate teaching knowledge and its application in the daily school life of the literacy teacher, with an emphasis on the challenges of continued training in Fortaleza. needs that arise in the daily life of literacy teachers, helping them to overcome the obstacles that limit their action and slow down the teaching-learning process of their students? Methodologically, this research is characterized by a descriptive and analytical study with a qualitative approach. As data collection, a semi-open questionnaire was used with literacy teachers who teach in schools that make up Regional V of the city of Fortaleza-Ce. The results indicate that continued training presents itself as a beneficial aid in the teacher's performance in the classroom, however, it is necessary that the topics covered are more diverse. It is concluded that it is important that the topics covered in the training effectively contribute to the teacher's teaching practice, boosting their participation in the training for the exchange of experiences and dialogue in order to provide opportunities for cooperation and sharing.